2020
DOI: 10.1177/1938640020913126
|View full text |Cite
|
Sign up to set email alerts
|

Short- to Midterm Follow-up of Cemented Total Ankle Replacement Using the INBONE II: A Retrospective Chart Review

Abstract: Background: Total ankle arthroplasty is a viable option for the treatment of end stage ankle arthritis. The purpose of this study is to report on the mid-term results with a cemented total ankle prosthesis, the Inbone™ II implant over a 5 year period. Methods: A retrospective, single-center chart and radiographic review of all patients with end stage ankle arthritis treated with Inbone™ II TAR) as the primary index procedure from 12/1/2012 to 3/1/2017. Clinical data were evaluated at 3 month, 6 month, 1 year a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…They were promptly detected and treated accordingly, and they all recovered well. No serious complications occurred in our cohort group, and this result is close to previous studies [ 13 15 , 24 ] . Among them, three patients with medial malleolus fractures all had osteoporosis, two were post-menopausal women, and one was a man with traumatic arthritis and had disuse osteoporosis due to long-term crutches.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…They were promptly detected and treated accordingly, and they all recovered well. No serious complications occurred in our cohort group, and this result is close to previous studies [ 13 15 , 24 ] . Among them, three patients with medial malleolus fractures all had osteoporosis, two were post-menopausal women, and one was a man with traumatic arthritis and had disuse osteoporosis due to long-term crutches.…”
Section: Discussionsupporting
confidence: 92%
“…Research by Rushing et al [ 15 ] showed that 7 years after INBONE-II prosthesis replacement, the prosthesis survival rate reached 93.7%, and the complication rate was 33.3%. The case series of Berlet et al [ 24 ] showed that the 2.4-year implant survival rate after INBONE-II prosthesis replacement was 95.0%, and the complication rate was 24.8%. Therefore, we believe that the short-term complication rate of TAR with INBONE-II prosthesis is relatively low, and the survival rate of the prosthesis is relatively high.…”
Section: Discussionmentioning
confidence: 99%
“…With the advancement of ankle protheses, total ankle arthroplasty (TAA) strengthens its trend as the procedure of choice for the older patient with end-stage ankle arthritis. 1 , 4 , 20 However, because of its posttraumatic nature, ankle arthritis remains a complex disease with onset in the third or fourth decade with dramatic quality of life effects similar to those found in older hip and knee arthrosis populations. 13 , 24 , 29 Current insight toward the physical and mental outcomes of patients receiving a TAA, along with componentry improvement, presents the question, Should younger patients be offered an ankle replacement?…”
Section: Introductionmentioning
confidence: 99%
“…All prostheses were placed using standard operative techniques. 13 Implantation of the tibial, talar, and polyethylene components were performed successively. Final anteroposterior and lateral radiographs were taken intraoperatively.…”
Section: Methodsmentioning
confidence: 99%
“…At this moment, the lower limb was placed into the external fixation jig according to the manufacturer's guidelines and technique for the INBONE II TAR implant. All prostheses were placed using standard operative techniques 13 . Implantation of the tibial, talar, and polyethylene components were performed successively.…”
Section: Methodsmentioning
confidence: 99%